EFFECT OF HARVESTING TIME ON HEMP (CANNABIS SATIVA L.) SEED OIL LIPID COMPOSITION - MARZOCCHI, S.; CABONI, M.F. (Italian Journal of Food Science, 2020)
The most common food using hemp (Cannabis sativa L.) is hempseed oil (HSO) because it is a rich source of nutrients with nutritional and functional beneficial effects for human body. Harvesting time can affect the quality of HSO, consequently the aim of this study was to evaluate the composition of lipid fraction, fatty acids, tocopherols and sterols, during ripening. Two cultivars, Futura 75 and Carmagnola, were collected at three ripening stages during August and September 2015 and their lipid composition was determined by analytical techniques. Among the fatty acid identified, the linoleic acid was the preponderant, followed by oleic, a-linolenic and palmitic acid. Linoleic:a-linolenic acid and polyunsaturated:saturated fatty acid ratios decreased and increased, respectively, in both varieties with ripening. y-tocopherol was the preponderant tocopherol identified, Futura 75 showed the highest content in the middle of maturation while Carmagnola at the beginning. B-sitosterol was the predominant sterol identified in both varieties, followed by campesterol, 5-avenasterol, stigmasterol and 7-stigmasterol. Total sterol content increased and decreased with ripening in Futura 75 and Carmagnola, respectively. The study confirms that ripening stage affects the quality of hempseed oil, important parameter to consider for hemp seed producers.